2020
DOI: 10.3354/esr01053
|View full text |Cite
|
Sign up to set email alerts
|

Assisted colonisation trials for the western swamp turtle show that juveniles can grow in cooler and wetter climates

Abstract: Species with restricted ranges and long generation times are vulnerable to climate change due to limited opportunity to disperse or adapt. Australia’s rarest reptile, the western swamp turtle Pseudemydura umbrina, persists naturally in only one seasonal swamp that holds water in the Austral winter and spring. A marked reduction in winter rainfall in recent decades has shortened the swamp hydroperiod, restricting when turtles are able to feed, grow and reproduce. To mitigate possible future loss of reproductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 46 publications
1
35
0
Order By: Relevance
“…To combat emerging threats, increasingly more extensive ecosystem manipulations are suggested, including assisted colonisation (Brodie et al, 2021), the translocation of individuals outside of their established range as a response to threats such as climate change (IUCN/SSC, 2013). These sorts of translocations, moving organisms outside of both their current and indigenous ranges are inherently extrapolative, as managers are knowingly creating unprecedented conditions and ecological interactions (Rendall et al, 2018;Bouma et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To combat emerging threats, increasingly more extensive ecosystem manipulations are suggested, including assisted colonisation (Brodie et al, 2021), the translocation of individuals outside of their established range as a response to threats such as climate change (IUCN/SSC, 2013). These sorts of translocations, moving organisms outside of both their current and indigenous ranges are inherently extrapolative, as managers are knowingly creating unprecedented conditions and ecological interactions (Rendall et al, 2018;Bouma et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We urge caution in the application of extrapolative translocation strategies, particularly with regard to assisted colonisation and rewilding projects that seek to create novel ecosystem conditions (Corlett, 2016). In these cases, where there is so much inherent uncertainty, we suggest that decisions should always be informed by what data are available, and that even the most experimental translocations should be based on evidencebased hypotheses regarding the potential success and risks of the translocation (Armstrong and Seddon, 2008;Bouma et al, 2020). This is due to the cautionary tales from the field of invasive species management, in which many species that have been introduced outside of their native range, whether accidentally or intentionally, are a major driver of ecosystem degradation and biodiversity decline, costing conservation management vast resources to reduce and reverse the resulting damage (Brook et al, 2008;O'Donnell et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…At Moore River and East Augusta this may reflect the shrinking size of wetlands as spring progressed, leading to a concentration of aquatic invertebrates and vertebrates. Meerup, in contrast, receiving higher than average rainfall in 2016 (Bouma et al, 2020), had a higher water level in late spring, and a lower concentration of aquatic animals.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may have been caused by the development cycle of different frog species: by late spring many tadpoles may already have developed into frogs in the latter wetlands. The higher richness of invertebrates in Moore River Nature Reserve compared with the southern sites might be attributed to warmer shallow water conditions (Bouma et al, 2020) and the relatively wet winter and spring in 2016: in 2016 Moore River received 743.4 mm, the highest annual rainfall since 1999 although the July to December rainfall was slightly below average (Bureau of Meteorology Perth, 2017). Crayfish, some of which can be predators of P. umbrina (Bradsell et al, 2002), were also found in Meerup and East Augusta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation